Band Spotlight: Starlift - Unknown (Pan Evolution)
Starlift Steel Orchestra was formed in 1956 when the members of three small bands from Woodbrook came together to start their own orchestra. While the band has a very colourful history, Starlift has been producing mas from its inception and won several Band of the Year titles over the years. Starlift has an impressive record in relation to its participation in mas. Starlift continues to stand out as one of the most revered steel orchestras, not only in Trinidad, but the world over.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Carnival -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago